Rwanda : Poverty Reduction Strategy Paper Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
The study analyzes the key elements of the poverty reduction strategy, including the participatory approach, donor coordination, growth-enhancing policies, and accountability and governance issues. A training program for government accountants has started, and the law establishing the office of the Ombudsman has been gazetted. The annual progress report acknowledges the need for an acceleration of structural reforms. New health and agricultural strategies are expected to revive and refocus the momentum in these critical sectors. However, poverty still affects two-thirds of the population, particularly in rural areas, and capacity constraints remain a major obstacle for reform implementation.